Gender and race disparities in the prevalence of chronic kidney disease among individuals with hypertension in the United States, 2001–2016 - Shen, Jing; Wang, Baoquan; Jing, Li; Chen, Tiancong; Han, Li; Dong, Weiwei (Frontiers in Endocrinology, 2024)
Chronic kidney disease (CKD) is a common complication among individuals with hypertension. We aimed to identify the prevalence of CKD and the sex and race disparities within the hypertensive population in the United States from 2001-2016. A total of 16,148 participants with hypertension were included, representing 561,909,480 individuals from the U.S. population between 2001 and 2016, as documented in the National Health and Nutrition Examination Survey. The prevalence of albuminuria and CKD stage were assessed using survey-weighted general linear regression analysis. Heterogeneity in the CKD stage among the hypertensive population, stratified by sex and race, was identified through survey-weighted logistic regression analysis. Overall, the prevalence of albuminuria remained stable (p for trend = 0.3196), and changes in the CKD stage were minimal (p for trend > 0.05) from 2001-2016. In the analysis of CKD stage heterogeneity by sex and race, the prevalence of CKD was higher among women than men and higher among individuals of other races combined than non-Hispanic Whites, but the differences were not statistically significant. The overall CKD stage within the hypertensive population plateaued between 2001 and 2016. Our findings highlight the importance of continuous monitoring and potential refinement of renoprotection strategies in individuals with hypertension to mitigate the persistent burden of CKD and address health disparities among different demographic groups.